Rancang Bangun Aplikasi Akuntansi Pengelolaan Dana Desa Berbasis Web Pada Kantor Kepala Desa Muara Lematang - Hairunnisa Hairunnisa; Iwan Setiawan; Rishi Suparianto (Jurnal Publikasi Teknik Informatika, 2023)
The web-based Village Fund Management Accounting application has been designed to increase efficiency and transparency in managing village funds at the Muara Lematang Village Head's Office. This study aims to develop a system that facilitates the process of recording, reporting, and monitoring village finances in real-time. The research methods used include literature studies, needs analysis, system design, and implementation. A literature study was conducted to understand the existing accounting application models and features relevant to the needs of village fund management. At the needs analysis stage, data was collected through interviews with village finance officers and analysis of documents related to village fund management. From the results of the analysis, it was found that several important features that must be owned by an application, including recording transactions, preparing financial reports, budget management, and monitoring the realization of funds. Based on the needs analysis, a system design was carried out by developing an intuitive and responsive user interface design. In addition, a database was also designed to store and manage village financial data in a safe and structured manner. At the implementation stage, a web-based village fund management accounting application has been successfully developed and tested at the Muara Lematang Village Head's Office. The trial was carried out by involving users involved in managing village funds to evaluate the performance and usability of the application. The results of this study indicate that web-based village fund management accounting applications can increase efficiency and transparency in village fund management. The use of this application can assist the Muara Lematang Village Chief's Office in keeping accurate records, compiling financial reports quickly, and monitoring the allocation and realization of village funds more effectively.